Description of two new species of the genus Siniassus (Hemiptera: Cicadellidae: Iassinae: Hyalojassini) from China - Yang, Hui-Ying; Dai, Ren-Huai (Zootaxa, 2022)
Two new species of leafhoppers: Siniassus gracilitus sp. nov. and S. nigrimaculatus sp. nov., of tribe Hyalojassini, subfamily Iassinae (Hemiptera: Cicadellidae) are described and illustrated from China. A key to Siniassus species and updated checklist with distributions are provided.